Estimation of Geothermal Energy Potential Using Monte Carlo Simulation at Jaboi Geothermal Field, Indonesia - Darisma, Dian; Turhamun, Rais Amsal; Masrurah, Zakia; Salsabila, Rifa Salma; Marwan, Marwan (Diponegoro University Semarang Indonesia, 2026)
Geothermal energy is an alternative solution for countries looking for renewable energy. However, energy potential estimation must be estimated before a drilling step to avoid drilling failure or financial loss. Monte Carlo simulation can be performed coupled with a volumetric method to calculate geothermal energy potential. This study aims to estimate the geothermal energy potential of the Jaboi geothermal field. The parameters used in this study were derived from previous studies and various references. Two scenarios are designed to extract the geothermal energy over 25 and 30 years. For the first scenario, 25 years, we obtained 34,51 MWe (P10), 48.28 MWe (P50), and 67.45 MWe (P90). For the second scenario, 30 years, we obtained 28.84 MWe (P10), 40.19 MWe (P50), and 56.20 Mwe (P90). The sensitivity analysis was then performed to determine which parameters significantly affect geothermal energy estimation. The results indicate that reservoir thickness is the most sensitive parameter. Therefore, determining this parameter must be done carefully.